2018
DOI: 10.1007/s00426-018-1009-4
|View full text |Cite
|
Sign up to set email alerts
|

The unimanual handle-to-hand correspondence effect: evidence for a location coding account

Abstract: The handle-to-hand correspondence effect refers to faster and more accurate responses when the responding hand is aligned with the graspable part of an object tool, compared to when they lay on opposite sides. We performed four behavioral experiments to investigate whether this effect depends on the activation of grasping affordances (affordance activation account) or is to be traced back to a Simon effect, resulting from the spatial coding of stimuli and responses and from their dimensional overlap (location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
(113 reference statements)
6
7
1
Order By: Relevance
“…In line with Roest et al ( 2016 ) and Pellicano et al ( 2018 ), as well as with the classic SE literature, our analyses failed to reveal any significant H-H compatibility effect in the participants’ LTs and MTs in both experiments. In contrast, the analyses on the spatial coordinates indicated that the endpoints of reach-to-touch movements are affected by three components that interact with each other: the response hand, the position of the handle in relation to the object body, and the handle orientation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with Roest et al ( 2016 ) and Pellicano et al ( 2018 ), as well as with the classic SE literature, our analyses failed to reveal any significant H-H compatibility effect in the participants’ LTs and MTs in both experiments. In contrast, the analyses on the spatial coordinates indicated that the endpoints of reach-to-touch movements are affected by three components that interact with each other: the response hand, the position of the handle in relation to the object body, and the handle orientation.…”
Section: Discussionsupporting
confidence: 89%
“…Within this debate, some authors have tried to dissociate the spatial and motor accounts by using go/no-go tasks, that is, tasks in which the SE is traditionally absent, with handled objects. In this regard, Roest et al ( 2016 ) reported a reversed H-H compatibility effect (Experiment 2), or no effects (Experiment 3), while Pellicano et al ( 2018 ) reported null compatibility effects in both Experiments 1A and 2A, where they manipulated the type of response (button-press or grasping). Overall, results from these two studies are in line with the spatial coding account, as the activation of motor affordances should be independent of the presence of right-left alternative responses.…”
Section: Introductionmentioning
confidence: 99%
“…A set of seven experiments was performed that clearly showed a spatial correspondence effect between the lateralized button press responses and the location of the spout. Thus, when salience was not a property of the graspable parts of the objects anymore, and the same objects appeared asymmetric because of another spatially distinctive portion, correspondence effects were driven by this second portion, thus clearly supporting the location coding account for object-based spatial correspondence effects (see also Pellicano et al 2018a). This is also the case when an object stimulus is centered on the screen so that its base or most of its body protrudes on the left/right rather than its handle (Pellicano et al 2018b;Proctor et al 2017).…”
Section: Introductionsupporting
confidence: 52%
“… 3. Recent findings have challenged the “automatic motor-program activation” interpretation of the orientation effect reported in this paradigm in favor of the more parsimonious location coding account (e.g., see Pellicano et al, 2019; for a review, see Osiurak & Badets, 2016). …”
mentioning
confidence: 96%